2012
DOI: 10.1214/12-aos992
|View full text |Cite
|
Sign up to set email alerts
|

Identifying locally optimal designs for nonlinear models: A simple extension with profound consequences

Abstract: We extend the approach in [Ann. Statist. 38 (2010Statist. 38 ( ) 2499Statist. 38 ( -2524 for identifying locally optimal designs for nonlinear models. Conceptually the extension is relatively simple, but the consequences in terms of applications are profound. As we will demonstrate, we can obtain results for locally optimal designs under many optimality criteria and for a larger class of models than has been done hitherto. In many cases the results lead to optimal designs with the minimal number of support poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 11 publications
2
63
0
Order By: Relevance
“…Checking whether Q(τ ) satisfies their conditions may be used to compute easily D-optimal and c-optimal designs. Moreover, the complete class of results given by Yang (2010), Yang and Stufken (2012), Dette and Melas (2011), Dette and Schorning (2013) can be applied to prove that the optimal designs have two support points, one of which is a boundary point for given models with two parameters. Otherwise the equivalence theorem will be checked for each particular case.…”
Section: Type I Censoring and Known Variancementioning
confidence: 99%
“…Checking whether Q(τ ) satisfies their conditions may be used to compute easily D-optimal and c-optimal designs. Moreover, the complete class of results given by Yang (2010), Yang and Stufken (2012), Dette and Melas (2011), Dette and Schorning (2013) can be applied to prove that the optimal designs have two support points, one of which is a boundary point for given models with two parameters. Otherwise the equivalence theorem will be checked for each particular case.…”
Section: Type I Censoring and Known Variancementioning
confidence: 99%
“…Hence, the group testing model satisfies the conditions for Theorem 2(a) in Yang & Stufken (2012), and therefore the designs having at most two points together with the designs having three points including x L (which coincides with a = 1) form an essentially complete class. In addition, according to the proof of Theorem 2 in Yang & Stufken (2012), it can be shown that there exists s 0 , …, s 5 = ±1 such that false{siΨifalse}i=05 is a chebyshev system on false[r,1false]. This property will be used in the proof of Theorem 3. …”
Section: Proof Of Theoremmentioning
confidence: 91%
“…Let 𝒞0=true{false{false(xi,wifalse)false}i=13:thinmathspacexL=x1<x2<x3xU,i=13wi=1,wi0true}. Note that by allowing w i = 0 at some points, this class contains all one- and two-point designs, and all three-point designs with a support point at x L . By applying Theorem 2(a) in Yang & Stufken (2012), we have the following theorem which allows us to search for a D - and a D s -optimal group testing design in 𝒞 0 …”
Section: The D- and Ds-optimal Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…One may then restrict oneself to this subclass Ξ com . Along this line, a series of remarkable papers by Yang and Stufken (2009), Yang (2010), Dette and Melas (2011), Yang and Stufken (2012) and Dette and Schorning (2013) derived several complete classes of designs for single response models with respect to the Loewner ordering of the information matrices, based on considerations of admissibility and invariance.…”
Section: Introductionmentioning
confidence: 99%